Study the Density of the Double Salt (Ammonium iron (II) sulfate) Dissolved in Water and Ethylene Glycol at Different Temperatures - Abood, Nagham H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Densities of double salt [(NH4)2Fe(SO4)2.6H2O] dissolved in distilled water and in ethylene glycol at three temperatures (298.15,303.15 and 308.15)k have been utilized to calculate the apparent molar volume , limiting apparent molar volume ,experimental slop . These results provide as information about solute-solvent, solute-solute interaction and structure-forming, structure-breaking tendency from partial molar expansibility .